GOOGLE APPS FOR EDUCATION (GAFE) DEMI PENINGKATAN KUALITAS PEMBELAJARAN ERA DIGITAL DI SMK DAR-EL HIKMAH PEKANBARU - Melly Novalia; Edi Ismanto; Vitriani Vitrian; Resmi Darni; Rahmad Alrian; Pratama Benny Herlandi (Jurnal Pengabdian UntukMu NegeRI, 2018)
The dedication to the community aims to provide training to all teachers at SMK Dar-el Hikmah Pekanbaru on the utilization of Google Apps for Education (GAFE) as a instructional medium in schools. The service method was conducted with training and evaluated regularly with the guidance of instructors from the Informatics Education Lecturer Team. As a result, all trainees get new knowledge about GAFE content such as Google Classroom, Google Form, Google Calendar and Google Drive. And also the school, hopes that there will be further training on developing the interactive instructional media.